2021
DOI: 10.3389/fpsyg.2021.662884
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Historical Change: An Emergent Cluster Led Uncles and Aunts to Become Aunts and Uncles

Abstract: There are times when a curiously odd relic of language presents us with a thread, which when pulled, reveals deep and general facts about human language. This paper unspools such a case. Prior to 1930, English speakers uniformly preferred male-before-female word order in conjoined nouns such as uncles and aunts; nephews and nieces; men and women. Since then, at least a half dozen items have systematically reversed their preferred order (e.g., aunts and uncles, nieces and nephews) while others have not (men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Binomials are coordinated word pairs belonging to the same word class, in our case nouns. Linguistic studies of binomials often focus on the degree of reversibility of binomials, i.e., the potential to change the order of the two elements (e.g., Molin 2014Molin , Čermáková 2021Goldberg & Crystal 2021). Of interest to our study is that binomials reflect interpersonal relationships between characters in the fictional worlds.…”
Section: Linguistic and Social Tiesmentioning
confidence: 99%
“…Binomials are coordinated word pairs belonging to the same word class, in our case nouns. Linguistic studies of binomials often focus on the degree of reversibility of binomials, i.e., the potential to change the order of the two elements (e.g., Molin 2014Molin , Čermáková 2021Goldberg & Crystal 2021). Of interest to our study is that binomials reflect interpersonal relationships between characters in the fictional worlds.…”
Section: Linguistic and Social Tiesmentioning
confidence: 99%
“…One line of research has explored the factors that determine the preferred order of binomials, particularly in terms of diachronic changes (e.g., Goldberg & Lee, 2021; Mollin, 2014). Goldberg and Lee (2021) found that binomials like uncles and aunts / nephews and nieces , which were in common use prior to the 1930s, have more recently reversed their preferred order to aunts and uncles / nieces and nephews. Goldberg and Lee proposed several cognitive explanations for the change, including the accessibility of the individual components of binomials in memory and their cluster strength.…”
Section: Introductionmentioning
confidence: 99%
“…But the usage-based nature of language is tacitly endorsed by nearly every psychologist and machine learning expert, as well as those of us who explicitly describe our perspective as usagebased (Abbot-Smith and Tomasello 2010; Ambridge and Lieven 2011; Arnon and Snider 2010;Boas 2008;Diessel and Hilpert 2016;Dunn 2019;Kidd, Lieven, and Tomasello 2010;Hilpert 2015;Ibbotson 2022). The frequencies of constructions and the frequencies of their subparts simultaneously influence language processing and language change (Baayen and Prado Martin 2005;Bybee, 2010;Goldberg and Lee 2021;Gries and Hilpert 2010;Traugott & Trousdale, 2013). And relationships among constructions and the forms of constructions are shaped by users goals and conversational demands over diachronic time (e.g., Francis & Michaelis 2017;DuBois, 2014;Givón, 2014).…”
mentioning
confidence: 99%